Evolution and Impact of Ventricular Assist Device Program on Children Awaiting Heart Transplantation - Adachi, Iki; Khan, Muhammad S.; Guzmán-Pruneda, Francisco A.; Fraser, Charles D.; Mery, Carlos M.; Denfield, Susan W.; Dreyer, William J.; Morales, David L.S.; McKenzie, E. Dean; Heinle, Jeffrey S.; Fraser, Charles D. (The Annals of thoracic surgery, 2015)
We sought to evaluate the impact of the evolution of a pediatric mechanical circulatory support (MCS) program on outcomes of children listed for heart transplantation at our institution. All patients listed for isolated heart transplantation from 1995 to 2013 were included. The use of MCS while on the wait-list was recorded. Wait-list and posttransplant outcomes were compared before and after 2005, which was when we became capable of providing long-term MCS without size limitation. In total, 259 patients were listed for transplant and 201 (78%) reached transplant. The use of MCS was significantly increased between the eras (13% and 37%, p = 0.0001). Wait-list mortality was significantly decreased (25% and 11%, p = 0.0006). Among transplant recipients, the proportion of patients who underwent MCS was significantly increased (13% and 37%, p = 0.0002). Of these MCS patients, the use of long-term devices was significantly increased (50% and 98%, p = 0.0004). Median duration of MCS was significantly increased (12 and 78 days, p = 0.004). Kaplan-Meier estimates showed a trend (p = 0.08) toward improved survival after bridge-to-transplant both at 1 year (70% in the early era and 88% in the late era) and at 5 years (60% and 78%, respectively). Outcomes of pediatric heart transplantation have significantly improved over the last 2 decades. We believe such improvement is, at least in part, attributable to maturation of MCS strategy, characterized by avoiding the use of temporary devices such as extracorporeal membrane oxygenation as a bridge-to-transplant and a more aggressive use of long-term devices.